Revestimento comestível incorporado com tocoferóis e aplicação em Castanhado-Brasil (bertholletia excelsa bonpl.) para monitoramento do perfil de oxidação lipídica - COSTA, Danusa Silva da (Universidade Federal do Pará, 2025)
Brazil nuts are a non-timber product of great importance to extractivist families. They contain many nutrients and are rich in lipids. However, from collection to oil extraction, Brazil nuts are exposed to various degrading conditions such as humidity, light, and heat due to exposure to the environment, and these conditions can intensify the lipid oxidation of this product. For this reason, developing an active coating is an alternative for protecting and preserving Brazil nuts from lipid oxidation. The aim was to develop an active edible coating incorporated with tocopherols and apply it to Brazil nuts to monitor their lipid oxidation profile at different storage times. Films were prepared by casting. Four blends, called B, L, LT, and LT2, were prepared using fixed amounts of cassava starch + carboxymethyl cellulose + sorbitol and water (3 g + 1.5 g + 0.2 g + 100 g, respectively), soy lecithin was added in a proportion of 20% in relation to the tocopherol mix, formulation L was prepared with the same amount of lecithin as LT2. The amount of tocopherol mix was added to the mixtures in the following proportions: B - 0, L - 0, LT - 0.0005 g, and LT2 - 0.010 g. Tests were carried out on thickness, water solubility, water content, weight, contact angle, permeability, mechanical tests, antioxidant activity, biodegradability, color, thermogravimetry, and FTIR. The films were characterized as biodegradable, antioxidant, and hygroscopic and suitable for application as a coating on Brazil nuts. Viscosity, creaming index, centrifugation, pH, and color of the solutions forming the coatings were evaluated, making it possible to characterize the blends as a non-Newtonian and highly stable pseudoplastic fluid. The Brazil nuts were immersed in the coating-forming solutions, dried at 45°C for 19 hours, stored at 25°C, and evaluated at 1, 7, 15, 30, 45, 60, 90, and 120 days of storage. By official methods, tests were carried out on mass loss, browning index, conjugated dienes and trienes, oxidative status, and accelerated oxidation index. All the coatings applied minimized oxidation at some stage during storage. However, the coatings added with the tocopherol mix minimized dienes, trienes, the iodine index, the peroxide index, p-anisidine, and the total oxidation index. The accelerated oxidation test showed that the nut oil under study underwent some changes in its oxidative state, although the use of the coatings largely preserved them. The models applied to the accelerated oxidation test data made it possible to estimate the half-life of the Brazil nuts, so it was found that the LT coating showed a value of 129.86h for the half-life time in the firstorder model. The principal component analysis (PCA) applied to the physicochemical characterization data and the induction time revealed that the oil from nuts uncoated presented itself in isolation as being extremely influenced by the oxidative indices evaluated, presenting an explained variability of the data greater than 75% in most of the storage times. PCA also showed that the oil from Brazil nuts coated with LT and LT2 was negatively influenced by most of the oxidative indices, in which case this is an advantage, as it demonstrates lower rates of lipid oxidation in these samples. Developing a film with antioxidant properties and applying it as a coating on Brazil nuts made it possible to verify some levels of protection for the nuts. We suggest applying the blends developed as a film or active coating to other food products that need protection against light and oxidation.